Yield and trace metal levels in rice (Oryza sativa) as influenced by flyash, fertilizer and farmyard manure application - KUMAR, ARVIND; SARKAR, A K; SINGH, R P; SHARMA, V N (The Indian Journal of Agricultural Sciences, 2013)
A field investigation on rice (Oryza sativa L) was carried out in rainy season (kharif) 1994 to study the influence of flyash, fertilizer and farmyard manure application on yield and trace metal content in rice and its availabiliy in soil. Flyash, fertilizer and farmyard manure application in soil significantly increased the yield of rice over the control, but fertilizer along with flyash proved to be superior to that with application of flyash and manure. Trace metal content in rice grain at 50 and 100% NPK level in combination with 10 tounes of farmyard manure did not vary significantly at 4 and 8% flyash. Nickel content of rice grain (7.6 mg/kg) showed a significant increase at 8% level of flyash addition compared with 4% level (4.4 mg/kg). Total uptake of some heavy metals (pb, Ni and Co) by rice grown in 4 and 8% flyash amended soil were higher compared with the farmyard manure treated plots or that not treated with flyash. Flyash did nbt significantly influence the availability of trace metals in soil. Results suggest that 4% flyash addition results in higher grain yields of rice without any possible trace metal contamination of soil and plant.